Should the ASEAN Regional Forum (ARF) Re-visit its Core Areas? - Karim, Mohd. Aminul (AEI Insights, 2021)
The ARF (ASEAN Regional Forum) projected three stages of its evolution, such as confidence-building, preventive diplomacy (PD), and “an approach to conflict”. The aim of this paper is to evaluate how far the ARF has gone beyond its first stage, as it is presumably hobbled by power-politics of big actors, lack of consensus in handling traditional security issues, and the presence of similar other security-related organizations in the region. That said, ARF’s outcome is impressive in sustaining confidence-building measures (CBM), and in fielding actionable projects in handling non-traditional security (NTS) issues, such as disaster management. Should not then The ARF devote more time and resource to NTS issues that will likely impact on traditional security in the long-run? This paper suggests certain action-oriented projects; basically that The ARF may not further deepen or widen geopolitically. Hence, the ARF continues to work as a traditional confidence-builder.